Cashier or Consultant? Entry Labor Market Conditions, Field of Study, and Career Success - Altonji, Joseph G.; Kahn, Lisa B.; Speer, Jamin D. (Journal of Labor Economics, 2016)
We measure impacts of entry conditions on labor market outcomes for the US college graduating classes of 1974–2011. A large recession reduces initial earnings by 10%, through full-time work and wages, with small persistent impacts on wages. Those in high-paying majors experience smaller impacts on most labor market outcomes, widening earnings inequality across majors. In the Great Recession, early earnings losses are much larger than predicted given past patterns and the size of the recession. This is partially because the cyclical sensitivity of demand for college graduates has more than doubled. Recession effects also became more evenly distributed across majors.